Pengaruh Pemanfaatan Internet sebagai Sumber Belajar terhadap Hasil Belajar Pendidikan Agama Islam di SMA Negeri 1 Tambang - Julia, Nur Annisa; Sari, Herlini Puspika; Mirawati, Mirawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aimed at testing the influence of internet utilization as a learning resource toward Islamic Education on learning achievement at State Senior High School 1 Tambang. Quantitative approach was used in this research with quasi experimental method. All the tenth-grade students were the population of this research, and they were 189 students. The samples were 64 students selected by using purposive sampling technique, 32 students were the experimental group, and 32 students were the control group. The techniques of collecting data were test and questionnaire. The technique of analyzing data was t-test analysis. Based on the research findings, it could be concluded that there was an influence of internet utilization as a learning resource toward Islamic Education learning achievement at State Senior High School 1 Tambang. It could be proven with the score of higher than (4.677>2.000). Student learning achievement was increased by utilizing the internet as a learning resource with the mean scores 79.56 in the experimental group and 70.97 in the control group.